The Nordic Maintenance Care Program – An interview study on the use of maintenance care in a selected group of Danish chiropractors - Møller, Lars Top (BioMed Central, 2009)
BACKGROUND: Although maintenance care appears to be relatively commonly used among chiropractors, the indications for its use are incompletely understood. A questionnaire survey was recently carried out among Swedish chiropractors in order to identify their choice of various management strategies, including maintenance care. That study revealed a common pattern of choice of strategies. However, it would be necessary to verify these findings in another study population and to obtain some additional information best collected through an interview. OBJECTIVES: The main aim of the present study was to attempt to reproduce the findings in the Swedish study and to obtain more information on the use of maintenance care. METHOD: A group of 11 chiropractors were selected because they used maintenance care. They were interviewed using the questionnaire from the previous Swedish survey. The questionnaire consisted of a simple description of a hypothetical patient with low back pain and nine possible ways in which the case could develop ("scenarios"). They could choose between six different management strategies for each scenario. In addition, the chiropractors were encouraged to provide their own definition of maintenance care in an open-ended question. Interviews were taped, transcribed and analyzed. For the open-ended question, statements were identified relating to six pre hoc defined topics on the inclusion criteria/rationale for maintenance care, the frequency of treatments, and the duration of the maintenance care program. RESULTS: The open-ended question revealed that in patients with low back pain, maintenance care appears to be offered to prevent new events. The rationale was to obtain optimal spinal function. There appears to be no common convention on the frequency of treatments and duration of the treatment program was not mentioned by any of the interviewees. CONCLUSION: The results from the questionnaire in the Danish survey showed that the response pattern for the nine scenarios was similar to that obtained in the Swedish survey. There seems to be relative agreement between chiropractors working in different countries and sampled through different methods in relation to their choice of management strategies in patients with low back pain. However, more precise information is needed on the indications for maintenance care and its treatment program, before proceeding to studying its clinical validity.